PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN MINUMAN BUBBLE TEA ONEZO KETAPANG DI JAKARTA BARAT - Akpianto, Agung; Yulianto, Yulianto (JAMBIS : Jurnal Administrasi Bisnis, 2024)
Food and beverage business in Indonesia continues to show development as many innovations emerge. The large population and rapid economic development have made the food and beverage business becomes one of the most lucrative businesses in Indonesia. A large market will create great business competition. The company must be able to provide the best price and product quality. If the price offered is too high it will reduce the level of purchasing decisions, however, if the price offered is too low, there will be doubts about the quality of the product, which will reduce the level of purchasing decisions. This research aimed to know and analyze the influence of price and product quality on purchasing decision for Onezo Ketapang Bubble Tea Drink in West Jakarta. The sampling technique used was total sampling with a total of 60 respondents. Data collection techniques used observation and questionnaires. The results of this research showed that price partially had a positive and significant effect on purchasing decisions by 59.2% with a calculated t- value (6.923) > t-table (2.002). Product quality partially had a positive and significant effect on purchasing decisions by 37.3% with a calculated t-value (3.352) > t-table (2.002). Price and product quality simultaneously had a positive and significant effect on purchasing decisions by 66.0% and the f-table value (55.203) > f-count (3.16).